A multiphase, micro-scale PIV measurement technique for liquid film velocity measurements in annular two-phase flow. (January 2015) - Ashwood, A.C.; Vanden Hogen, S.J.; Rodarte, M.A.; Kopplin, C.R.; Rodríguez, D.J.; Hurlburt, E.T.; Shedd, T.A.
Highlights: Particle Image Velocimetry (PIV) is applied to the liquid film of annular flow. Unique experimental and software techniques that enable PIV in thin, wavy films. Mean velocity data are presented from within a 1–2 μm of the wall to 1 mm. Local wall shear estimated from the velocities shows 20% agreement with experiment. Turbulent boundary layer model predicts well using reduced turbulent diffusivity. Abstract: Prediction methods for two-phase annular flow require accurate knowledge of the velocity profile within the liquid film flowing at its perimeter as the gradients within this film influence to a large extent the overall transport processes within the entire channel. This film, however, is quite thin and variable and traditional velocimetry methods have met with only very limited success in providing velocity data. The present work describes the application of Particle Image Velocimetry (PIV) to the measurement of velocity fields in the annular liquid flow. Because the liquid is constrained to distances on the order of a millimeter or less, the technique employed here borrows strategies from micro-PIV, but micro-PIV studies do not typically encounter the challenges presented by annular flow, including very large velocity gradients, a free surface that varies in position from moment to moment, the presence of droplet impacts and the passage of waves that can be 10 times the average thickness of the base film. This technique combines the seeding and imaging typical to micro-PIV with a unique lighting and image processing approach to deal with the challenges of a continuously varying liquid film thickness and interface. Mean velocity data are presented for air–water in two-phase co-current upward flow in a rectangular duct, which are the first detailed velocity profiles obtained within the liquid film of upward vertical annular flow to the authors' knowledge. The velocity data presented here do not distinguish between data from waves and data from the base film. The resulting velocity profiles are compared with the classical Law of the Wall turbulent boundary layer model and found to require a decreased turbulent diffusivity for the model to predict well. These results agree with hypotheses previously presented in the literature.